PERAN TATA USAHA DALAM PENGELOLAAN ARSIP DI SD 9 TALANG KELAPA - Oktarina, Nining; Saputra, Ade Akhmad (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
To maintain the order, security and availability of documents that support the smooth operation of the school, effective records management is an important part of school management. This study discusses the role of the administration in managing records at SD 9 Talang Kelapa. Data were collected through observation, interviews and documentation using qualitative methods. The data analysis technique used was thematic analysis. This means that the data collected is grouped according to certain themes that have been discussed in the research. Then, patterns and relationships between data relating to the role of archive management were found. The research shows that the recording, storage, maintenance and presentation of school documents are strategically influenced by the administration. Good records management helps teachers, students and related parties get information more easily and helps make better decisions. However, there are several problems encountered, such as limited storage facilities, untrained workers, and a recording system that is still done manually. To overcome these problems, educational institutions have started to implement document digitisation and train administrative employees in managing archives. In addition, the government and schools should get further support to provide more sophisticated systems and facilities. The education process at SD 9 Talang Kelapa can run more smoothly with better records management.